University chemistry - Laird, Brian B. (McGraw-Hill, 2009)
This dynamic new Honors General Chemistry text brings together a practical “Molecular to Macroscopic” approach, a proven problem solving approach that challenges students to think logically, along with a clear and concise writing style. Combined with the author’s teaching experience at the University of Kansas, extensive reviewing and accuracy checks, Brian Laird’s University Chemistry is certain to meet the needs of both instructor and student.